The three billy goats gruff - Pinkney, Jerry; Asbjørnsen, Peter Christen, 1812-1885. (New York ; Boston : Little, Brown and Company, 2017)
Three billy goats must outwit the big, ugly troll that lives under the bridge they have to cross on their way up the mountain.
Keywords: Fairy tales; Folklore